2009
DOI: 10.1177/0095244308095014
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Sugarcane Bagasse Fiber—Thermoplastics Composites

Abstract: The influence of thermoplastic/bagasse fiber ratio, as well as electron beam irradiation on the physicomechanical properties of low-density polyethylene (LDPE) and high-density polyethylene (HDPE) composites has been investigated. The concentration of bagasse fibers ranges from 20 to 80 wt%. The results indicate that there is deterioration in the properties as fiber concentration increased; however, it becomes significant only beyond 50% (w/w) bagasse fibers in both LDPE and HDPE composites. Also, the data sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Due to the limitation of gamma irradiation such as time consuming and probability of severe oxidation degradation of the composites, electron beam irradiation (EBI) offers some advantages in comparison to other conservative alteration methods. 66 The advantages of EBI include: it provides reliable sterilisation; very high dose rates are achievable; radiation doses are easily controlled; safe and easy to operate; high speed enhancement of properties, allowing irradiation of a variety of physical shapes; and pose no serious environmental hazards due to practically free of waste products. [67][68][69] Usually, during EBI, polymers having hydrogen in their monomeric units tend to form crosslink whereas others might be degraded during irradiation.…”
Section: Radiation On Thermoplastic/natural Filler Compositesmentioning
confidence: 99%
“…Due to the limitation of gamma irradiation such as time consuming and probability of severe oxidation degradation of the composites, electron beam irradiation (EBI) offers some advantages in comparison to other conservative alteration methods. 66 The advantages of EBI include: it provides reliable sterilisation; very high dose rates are achievable; radiation doses are easily controlled; safe and easy to operate; high speed enhancement of properties, allowing irradiation of a variety of physical shapes; and pose no serious environmental hazards due to practically free of waste products. [67][68][69] Usually, during EBI, polymers having hydrogen in their monomeric units tend to form crosslink whereas others might be degraded during irradiation.…”
Section: Radiation On Thermoplastic/natural Filler Compositesmentioning
confidence: 99%
“…In this context, the aim of this work is to develop and evaluate the mechanical and thermal properties of the LDPE composites reinforced with fibers of Australia Royal Palm for Biosolvit company. LDPE have been widely used as matrix for obtaining composites reinforced with natural fibers: doum/LDPE [4], coconut/ LDPE [15], sugarcane bagasse/LDPE [16], cotton/LDPE [17] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Lazzeri et al [19] observed that uncoated precipitated CC particles have a very small nucleating effect on high density polyethylene (HDPE). LDPE is reported to have more amorphous phase than HDPE [20] [21]. For such semi-crystalline polymer based composites, fillers which can act as strong nucleating agent have the potential to induce polymer crystallization and also improve the interfacial interaction, which is the key to the preparation of high performance polymer/filler composites [22].…”
Section: Introductionmentioning
confidence: 99%